# Answer on Algebra Question for Tanveer

Question #11060

prove that, p(q^2+r^2)+q(p^2+r^2)+r(p^2+q^2)=0.

Expert's answer

If we denote

g1=p+q+r

g2=pq+qr+pr

g3=pqr

then

p(q^2+r^2)+q(p^2+r^2)+r(p^2+q^2)=g1*g2-3*g3

If

g1=g3=0 then given expression is zero too.

g1=p+q+r

g2=pq+qr+pr

g3=pqr

then

p(q^2+r^2)+q(p^2+r^2)+r(p^2+q^2)=g1*g2-3*g3

If

g1=g3=0 then given expression is zero too.

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment